Blind policy-maker: an empirical evidence from the Italian case - Carlo Tesauro (European Regional Science Association (ERSA), 2015)
The policy-maker is normally perceived as an institutional actor in the public sector by Italian citizens (Tesauro, 2011), while it really also includes individuals operating in private organizations which, by their nature, are strongly linked with the socio economic environment. The most obvious example of private policy-maker is represented by executives of companies for infrastructural services supply which, with their policies, generate significant impacts on the socio economic context (Campisi, Tesauro 1997) (Tesauro, 2007). In Italy, most of the infrastructure service companies, certainly the most important ones at the national level, were managed by public corporations until a few years ago, as for example: telephone, electricity, household gas, rail, highways, airlines, ferries and so on. For this reason, their activities were subject to the control of national policy and therefore, even if indirectly, to the control of the citizens, the 'policy-takers', through the normal tools of institutional democracy, as is the case for the activity of local authorities policy-makers ie municipalities, regions, provinces and so on. In recent years, however, the process of privatization of public enterprises has effectively removed from the policy, and thus indirectly from the citizens, the control over the policies adopted by these companies. This effect is further amplified by the fact that many of these activities are currently, or will be shortly, managed by companies with foreign capital, so increasing the distance with the subjects assigned to the control. In addition, the ranks of private organizations able to generate induced effects on the territory can be increased by a substantial number of companies linked to other economic sectors. Most of these companies operate in areas still subject to control and supervision, or only recently fully liberalized. These other companies, by mean of their pricing policies based on 'custom' criteria, can generate meaningful effects in the socio economic national context, so becoming real blind policy-makers. The objective of this paper is therefore to analyze an empirical case well known in Italy, the automobile insurance, to enhance the economic impact at local scale. The results will highlight that the different rates requested in ten italian provinces and their deviation from the national average value generate impacts of extremely significant values, proportional to the value of EU contributions to the development of regions.
Keywords: 330; Policy maker; Politics; Policies; Socio economic impact